2016
DOI: 10.4081/ija.2016.738
|View full text |Cite
|
Sign up to set email alerts
|

Water saving strategies assessment on processing tomato cultivated in Mediterranean region

Abstract: Processing tomato grown in Mediterranean region required high irrigation volume throughout growing season. A two-year study was carried out in order to investigate the effects of deficit irrigation (DI) and regulated deficit irrigation (RDI) on processing tomato cultivated under sub-arid conditions. A comparison between the irrigation management linked to common practice adopted by farmer and the irrigation management based on crop evapotranspiration (ETc) demand was also done. The tomato cv. Genius F1 was cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 29 publications
(46 reference statements)
2
26
0
Order By: Relevance
“…The tomato (Solanum lycopersicum L.) is one of the most important vegetable crops worldwide and one of the most demanding of water [7]. The seasonal water requirement for processing tomato is estimated to be approximately 5000 to 6000 m 3 ha −1 , which, in semi-arid areas, is almost totally supplied by irrigation [6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tomato (Solanum lycopersicum L.) is one of the most important vegetable crops worldwide and one of the most demanding of water [7]. The seasonal water requirement for processing tomato is estimated to be approximately 5000 to 6000 m 3 ha −1 , which, in semi-arid areas, is almost totally supplied by irrigation [6].…”
Section: Introductionmentioning
confidence: 99%
“…In these areas, due to climate change, the frequency and severity of prolonged periods of drought, as well as strong seasonal variation in the water budget, are predicted [2][3][4]. In this context, both use of the non-conventional waters (e.g., treated wastewater) and appropriate techniques of water saving, can be used to reduce the gap between the supply and demand of irrigation water [5,6]. The tomato (Solanum lycopersicum L.) is one of the most important vegetable crops worldwide and one of the most demanding of water [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results obtained by several researchers support the results obtained in this study. For example [50,27,22] , pointed out that the marketable yield under the FI treatment provided the highest values compared with RDI and PRD. Kuscu et al [51] reported that the highest marketable tomato yields were observed with FI, and decreasing the irrigation rate generally improved the dry matter of fresh tomato fruits.…”
Section: Resultsmentioning
confidence: 99%
“…Among all treatments over the two years, there are no significant effects (p>0.05) on IWUE values. Similarly, the effects of water stress on the IWUE have been pointed out by several researchers, and they noted that there were not any significant differences in IWUE among the different water regimes that they used [50,64] .…”
Section: Resultsmentioning
confidence: 99%